Contextualising Formal Education for Improved Relevance: A case from the Rufiji wetlands, Tanzania - Rose Hogan (Environmental Association of Southern Africa, 2008)
The aim of this action research case study was to engage a community of villagers, teachers, students and district officers in a participatory process to adapt a module of a school curriculum to the local context, and teach it in order to describe one way in which contextualisation, using local and indigenous knowledge and active discovery teaching-learning processes, can be done. The major research question was: Does integrating local environmental cultural knowledge into formal schooling contribute to curriculum relevance? If so, in what way? This paper summarises the background and context of the research, the motivation and the theoretical basis for the work, the methodology and methods, and the action research process itself. The results are interpreted and discussed in light of current theoretical perspectives on education and environmental education. The main findings within the case are that contextualisation improved relevance of education and thus its quality by: • Breaking through traditional frames/barriers between teachers and students, students and elders and community and teachers. • Allowing formal education to take place outside of the school. • Necessitating a change in pedagogy to more learner-centred discovery methods. • Allowing indigenous knowledge to come into the classroom. • Stimulating creativity and increased confidence. • Bringing local socio-political environmental issues into the classroom.